A digital technique for replicating peri-implant soft tissue contours and the emergence profile - Liu, Xiaoqiang; Liu, Jianzhang; Mao, Hong; Tan, Jianguo (The Journal of prosthetic dentistry, 2017)
A digital technique is presented that records peri-implant soft tissue contours and the emergence profile. The architecture of interim restorations and adjacent teeth, the position of the implant, and the emergence profile of interim prostheses are scanned and registered to design a zirconia frame and to form a digital cast.